Prevalence of sexually transmitted infections among pregnant women with known HIV status in northern Tanzania - Mbizvo Elizabeth M; Hussain Akhtar; Uriyo Jacqueline; Msuya Sia E; Jeansson Stig; Sam Noel E; Stray-Pedersen Babill (BMC, 2009)
Abstract Objectives To determine the prevalence of sexually transmitted infections (STIs) and other reproductive tract infections (RTIs) among pregnant women in Moshi, Tanzania and to compare the occurrence of STIs/RTIs among human immunodeficiency virus (HIV)-infected and uninfected women. Methods Pregnant women in their 3rd trimester (N = 2654) were recruited from two primary health care clinics between June 2002 and March 2004. They were interviewed, examined and genital and blood samples were collected for diagnosis of STIs/RTIs and HIV. Results The prevalence of HIV, active syphilis and herpes simplex virus - type 2 (HSV-2) were 6.9%, 0.9% and 33.6%, respectively, while 0.5% were positive for N gonorrhoeae, 5.0% for T vaginalis and 20.9% for bacterial vaginosis. Genital tract infections were more prevalent in HIV-seropositive than seronegative women, statistically significant for syphilis (3.3% vs 0.7%), HSV-2 (43.2% vs 32.0%), genital ulcers (4.4% vs 1.4%) and bacterial vaginosis (37.2% vs 19.6%). In comparison with published data, a declining trend for curable STIs/RTIs (syphilis, trichomoniasis and bacterial vaginosis) was noted. Conclusion Rates of STIs and RTIs are still high among pregnant women in Moshi. Where resources allow, routine screening and treatment of STIs/RTIs in the antenatal care setting should be offered. Higher STIs/RTIs in HIV-seropositive women supports the expansion of HIV-counseling and testing services to all centers offering antenatal care. After identification, STIs/RTIs need to be aggressively addressed in HIV-seropositive women, both at antenatal and antiretroviral therapy care clinics.